Modeling population immunity to support efforts to end the transmission of live polioviruses - Thompson, Kimberly M. (Risk Anal, 2012)
Eradication of wild poliovirus (WPV) types 1 and 3, prevention and cessation of circulating vaccine-derived polioviruses, and achievement and maintenance of a world free of paralytic polio cases requires active risk management by focusing on population immunity and coordinated cessation of oral poliovirus vaccine (OPV). We suggest the need for a complementary and different conceptual approach to achieve eradication compared to the current case-based approach using surveillance for acute flaccid paralysis (AFP) to identify symptomatic poliovirus infections. Specifically, we describe a modeling approach to characterize overall population immunity to poliovirus transmission. The approach deals with the realities that exposure to live polioviruses (e.g., WPV, OPV) and/or vaccination with inactivated poliovirus vaccine provides protection from paralytic polio (i.e., disease), but does not eliminate the potential for re-infection or asymptomatic participation in poliovirus transmission, which may increase with time due to waning immunity. The AFP surveillance system provides evidence of symptomatic poliovirus infections detected, which indicate immunity gaps after outbreaks occur, and this system represents an appropriate focus for controlling disease outbreaks. We describe a conceptual dynamic model to characterize population immunity to poliovirus transmission that helps identify risks created by immunity gaps before outbreaks occur, which provides an opportunity for national and global policy makers to manage the risk of poliovirus and prevent outbreaks before they occur. We suggest that dynamically modeling risk represents an essential tool as the number of cases approaches zero.